2020
DOI: 10.1016/j.ymgme.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease during the COVID-19 pandemic. Why and how treatment should be continued

Abstract: Fabry disease is an X-linked disease due to a deficiency of the lysosomal enzyme alpha-galactosidase A. Clinical symptoms in classically affected males include acroparesthesia, anhydrosis and angiokeratoma, which may present during childhood followed by cardiac, cerebral and renal complications. Even though pulmonary involvement is not widely appreciated by clinicians, an obstructive lung disease is another recognized component of Fabry disease. Coronavirus Disease-19 (COVID-19), caused by the SARS-CoV-2 virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Little is known about SARS-CoV-2 infection in children with comorbidities (such as congenital heart, lung and airway diseases, chronic heart and kidney diseases, malnutrition, tumors, diabetes, immunodeficiency or hypoimmunity) and little information is available on the effects of the infection in pediatric patients with congenital inborn errors of metabolism (IEM) [ 8 , 12 ]. However, emerging guidelines have been proposed to manage eventual SARS-Co V2 infection in lysosomal diseases and on inherited heart diseases [ 13 15 ]. In addition, it has been reported that a patient affected by mucolipidosis type II died because of pneumonia complicated by acute respiratory distress syndrome (ARDS) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about SARS-CoV-2 infection in children with comorbidities (such as congenital heart, lung and airway diseases, chronic heart and kidney diseases, malnutrition, tumors, diabetes, immunodeficiency or hypoimmunity) and little information is available on the effects of the infection in pediatric patients with congenital inborn errors of metabolism (IEM) [ 8 , 12 ]. However, emerging guidelines have been proposed to manage eventual SARS-Co V2 infection in lysosomal diseases and on inherited heart diseases [ 13 15 ]. In addition, it has been reported that a patient affected by mucolipidosis type II died because of pneumonia complicated by acute respiratory distress syndrome (ARDS) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current available data about the impact of COVID-19 on patients suffering from inborn errors of metabolism are very scarce. Published data concerning the pandemic are mainly reports describing expert opinions about management challenges and guidelines for IEM disorders [ [7] , [8] , [9] , [10] ], and few patient surveys investigating management problems and satisfaction [ [11] , [12] , [13] ]. Case reports of IEM patients with confirmed viral infection have also been published recently [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Long and/or short‐term ERT interruptions are common events mainly among patients from low and middle‐income countries. Furthermore, during this year's COVID‐19 pandemic, patients with rare diseases worldwide were compelled to discontinue treatment at hospitals or health care facilities to minimize their risk of infection and consequent severe illness 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during this year's COVID-19 pandemic, patients with rare diseases worldwide were compelled to discontinue treatment at hospitals or health care facilities to minimize their risk of infection and consequent severe illness. 17,18 To date, there are no published reports regarding the effects of ERT discontinuation on MPS IVA patients. Studies on other types of MPS have shown that ERT interruption may reverse its beneficial effects and, in some cases, even worsen clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%